Tempranillo physiological and agronomical responses to heat and drought stress – perspectives on its vulnerability under climate change scenarios - Lopes, C.M. (2022)
With the aim to characterize the ability of Tempranillo grapevines, one of the most widely used varieties in Spain and Portugal, to withstand drought and heat stress, ecophysiological and agronomical data from irrigation experiments conducted in the hot and dry region of Alentejo, south of Portugal, are presented. The impact of different irrigation treatments on physiological parameters (leaf water potential, photosynthesis, and stomatal conductance) and water use efficiency are showed. Leaf senescence observed in non-irrigated and deficit irrigated plants and its consequences on cluster exposure and berry temperature are compared with those of fully irrigated plants. The consequences on berry ripening and juice composition are discussed in order to evaluate the vulnerability of Tempranillo to the expected global climatic change